2021
DOI: 10.36079/lamintang.ijeste-0401.195
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mobile-Based Assessment Acceptance Studies from 2009 To 2019

Abstract: Despite many studies being conducted on mobile learning acceptance, few investigate mobile-based assessment acceptance. The objectives of this research are to provide valuable insights into current research on mobile-based assessment literature, and to identify the main gaps in the mobile-based assessment acceptance literature. Therefore, the present study systematically reviews 48 previous studies and eight articles related to mobile-based assessment acceptance to provide a comprehensive analysis of the artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Mobile devices provide a time‐ and location‐independent medium and facilitate the implementation of mobility‐based assessments (MBAs) that complement paper‐ and computer‐based assessments (Alrfooh & Lakulu, 2021; Nikou & Economides, 2018). Compared with paper‐ and computer‐based assessments, MBAs enable a more flexible assessment arrangement and more opportunities for peer interactions, feedback, and scaffolding (Nikou & Economides, 2017; Nikou & Economides, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile devices provide a time‐ and location‐independent medium and facilitate the implementation of mobility‐based assessments (MBAs) that complement paper‐ and computer‐based assessments (Alrfooh & Lakulu, 2021; Nikou & Economides, 2018). Compared with paper‐ and computer‐based assessments, MBAs enable a more flexible assessment arrangement and more opportunities for peer interactions, feedback, and scaffolding (Nikou & Economides, 2017; Nikou & Economides, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with paper‐ and computer‐based assessments, MBAs enable a more flexible assessment arrangement and more opportunities for peer interactions, feedback, and scaffolding (Nikou & Economides, 2017; Nikou & Economides, 2018). Although MBA is still in its infancy (Bacca‐Acosta & Avila‐Garzon, 2021), it has been used and studied extensively (Alrfooh & Lakulu, 2021; Nikou & Economides, 2018). However, Bacca‐Acosta and Avila‐Garzon (2021) found that students are highly likely to discontinue use within the first 25–50 minutes of using MBA.…”
Section: Introductionmentioning
confidence: 99%